Design of Teaching Materials and Toys for Early Childhood to Development Skills for 2nd year Early Childhood Education Students - Karaket ์Natthiyaporn (Journal of Modern Learning Development, 2022)
This research aims to Develop skills in making media and toys for early childhood. by designing media and toys for early childhood education students This research is an experimental research. The sample consisted of 56 students in the field of early childhood education enrolled in art courses for early childhood teachers in the second semester of the academic year 2021 at the Faculty of Education, Thepsatri Rajabhat University. research tools is an assessment of the design and construction of media and toys for early childhood. Statistics used in research average percentage The results showed that media and toys design for preschool children in terms of activities, vegetable and fruit set, mean 9.6, pizza set, mean 8.4, ice cream set, crepe set, mean 8.0, pancake set, Mala set, noodle set. Average 7.8, Meatball Set, Dim Sum Set, Average 7.6, Khanom Krok Set, Toast Set, Bingsu Set, Average 7.4, Gift Shop, Average 7.2, Steak Set, Average 6.8, Egg Pan Set, Average 6.6, and Hamburger Set. with a mean score of 6.4, with a mean total of 7.61 activity sets, and design of early childhood media and toys. Creativity was an average of 8.41, learning promotion was an average of 7.41, media benefit was an average of 7.52, durability. and sophistication, with an average of 7.35 and an overall average of 7.61.